The Effect of Financial Controls on Financial Performance of Local Government Units in Ghana - Musah, Alhassan; Odei Okyere , Daniel; Wellington Blay, Marshall; Emilson Adenutsi , Deodat; Okyere , Bismark (International Journal of Economics and Financial Issues, 2025)
This study investigates the intricate relationship between financial controls and performance in the Metropolitan, Municipal, and District Assemblies (MMDAs) of Greater Accra, Ghana. Unlike profit-seeking businesses that prioritize generating shareholder value, non-profits such as MMDAs focus on meeting community needs. Using quantitative analysis through SPSS and AMOS software, the research employs a structural equation model and logistic regression model to examine various aspects of financial control and their impact on financial health. The key findings reveal that efficient reconciliations, robust audits, and sound payables management significantly enhance financial performance. However, a surprising negative association between weak monitoring and performance was also discovered, prompting further investigation. The study recommends optimizing reconciliation processes, strengthening audit practices, and improving payables management. Moreover, it emphasizes addressing deficiencies in financial monitoring through effective systems, trained personnel, and a culture of transparency. This holistic approach views financial controls as an interconnected system, whose harmonious interplay unlocks true financial potential and sustainability for MMDAs. The study concludes that optimizing financial control approaches is critical for MMDAs in Greater Accra to achieve thriving financial futures, highlighting the importance of balancing control elements and exploring deeper relationships within the system to unlock financial health and sustainable development.